Change of direction and deceleration deficits in adolescent male soccer players at different maturity levels - Sert, V.; Kaymakçi, A. T.; Gelen, E.; Yildiz, S. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Background Change of direction and deceleration are crucial for soccer performance. However, these abilities may be influenced by growth and maturation during adolescence. Understanding these effects is essential for optimizing training and potentially mitigate injury risk in young players. This study aimed to evaluate the effects of maturation on change of direction (COD) and deceleration performance in adolescent male soccer players with varying levels of maturity.